Wrong-site tooth extraction removed from the list of NHS never events – implications for OMFS. Issue 7 (September 2021) - Brennan, P.A.; Shakib, K.
Abstract: Never events that are relevant to OMFS include wrong-site procedures (including tooth extraction), and retained instruments and swabs. In February 2021, the list of never events was updated to exclude wrong tooth extraction, as the systemic barriers to prevent these incidents were not considered 'strong enough.' We discuss the matter, and provide some recommendations to minimise the risk of wrong tooth extraction, which to date has been the commonest never event in the NHS.